Single low-dose ketamine infusion for women with prenatal depressive symptoms undergoing cesarean delivery: A pilot randomized trial - Wang, Shuo; Deng, Chun-Mei; Zeng, Yuan; Ma, Jia-Hui; Qu, Yuan; Wang, Dong-Xin (Frontiers in Surgery, 2022)
Background Ketamine is approved for antidepressant therapy, but evidence regarding its use in women with perinatal depression is lacking. Herein, we investigated the effects of low-dose ketamine in women with prenatal depressive symptoms and tested the feasibility of a future large randomized trial. Methods This was a randomized, double-blind, placebo-controlled pilot trial. Sixty-six women with prenatal depressive symptoms who were scheduled for elective cesarean delivery were randomized to receive either low-dose ketamine (0.5 mg/kg) or placebo (normal saline). The study drugs were intravenously infused over a 40-minute period after clamping the umbilical cord. The primary outcome was depression score assessed with the Edinburgh Postnatal Depression Scale at 48 h postpartum. Among other and safety outcomes, occurrence of nausea or vomiting was observed, pain intensity was assessed with the numeric rating scale. The feasibility of implementing the protocol was also evaluated. Results A total of 64 parturients were included in the intention-to-treat analysis. The depression score at 48 h did not differ between groups: median 9 (interquartile range 6 to 13) with ketamine vs. 8 (6 to 10) with placebo; median difference 1, 95% CI −1 to 3; P = 0.608. The pain intensity at 4 h postpartum was less severe in the ketamine group (median difference −1, 95% CI −1 to 0, P = 0.002). Among safety outcomes, intraoperative nausea or vomiting was less common in patients given ketamine (0.0% [0/33] with ketamine vs. 21.2% [7/33] with placebo, P = 0.011). Recruitment was satisfactory and the protocol was acceptable to participants and clinicians. Conclusions A single low-dose ketamine infusion did not decrease the depression score at 2 days, but reduced intraoperative nausea and vomiting and lowered pain intensity at 4 h after cesarean delivery among women with prenatal depressive symptoms. The study protocol is feasible for a large randomized trial. Clinical Trial Registration The study was registered with ClinicalTrials.gov (identifier: NCT03336541; 08/11/2017).